How do you solve using gaussian elimination or gauss-jordan elimination, 2x + 4y−6z = 422x+4y6z=42, x + 2y+ 3z = 3x+2y+3z=3, 3x−4y+ 4z = −163x4y+4z=16?

1 Answer
Nov 20, 2017

The solution is ((x),(y),(z))=((4),(4),(-3))

Explanation:

Perform the Gauss Jordan elimination on the augmented matrix

A=((1,2,-3,|,21),(1,2,3,|,3),(3,-4,4,|,-16))

Perform the row operations

R2larrR2-R1 and R3larrR3-3R1

A=((1,2,-3,|,21),(0,0,6,|,-18),(0,-10,13,|,-79))

R2harrR3 and R3larr(R3)/6

A=((1,2,-3,|,21),(0,-10,13,|,-79),(0,0,1,|,-3))

R2larr(R2-13R3) and R2larr(R2)/(-10)

A=((1,2,-3,|,21),(0,1,0,|,4),(0,0,1,|,-3))

R1larr(R1-2R2) and R1larrR1+3R3

A=((1,0,0,|,4),(0,1,0,|,4),(0,0,1,|,-3))